We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
170
10
avatar

-5[x+(-7)]=49 <----- I feel like my setup is wrong. I don't even understand how to solve it.

 Feb 28, 2019
 #1
avatar+6045 
+2

\(-5(x+(-7)]=49\\ -5x + 35 = 49\\ -5x = 14\\ x = -\dfrac{14}{5}\)

.
 Feb 28, 2019
 #3
avatar+67 
-1

-14/5 is 2.8 just btw so u don't get confused

DivideByZero  Feb 28, 2019
 #4
avatar+4325 
+1

I think you mean -2.8.

tertre  Feb 28, 2019
 #6
avatar+67 
-1

yea i did sorry

DivideByZero  Feb 28, 2019
 #2
avatar+67 
-1

DON'T STRESS 

Look, I know it looks hard, but just power through and take it step by step

-5(x+[-7])=49

Distribute

-5x+35=49

    -35     -35

-5x=14

Divide

x=-2.8

-DBZ

wink

 Feb 28, 2019
edited by DivideByZero  Feb 28, 2019
 #5
avatar
+1

 

When the sum of a number and -5 is multiplied by -7, the result us 49.

 

How do you eat an elephant?  One bite at a time. 

Take this problem apart and look at one bite at a time.

 

"When the sum of a number and –5 is..."       What does this mean?  First, there's a number.  We don't know what it is so let's let X stand for it. So the sum of X and –5 is simply X +(–5), or X–5.  Put some parentheses around that, like this: (X–5)

 

What is the next part of the problem?  "...is multiplied by –7"  so let's write out that multiplication: (X–5)(–7)

 

The problem says that that equals 49, so put it all together           (X–5)(–7) = 49

 

Then just multiply the left side and the equation looks like this:       –7X + 35 = 49

 

Subtract 35 from both sides                                                              –7X = 14

 

Divide both sides by –7                                                                         X = –2 

 

.

 Feb 28, 2019
 #7
avatar+19686 
+1

Sum of a number and -5    ====   (x+-5)

    is multiplied by  -7        ======  7(x-5)

       the result is 49      =========== -7(x-5) = 49    use distributive property

                                                            -7x + 35 = 49    subtract 35 from both sides of the equation

                                                             -  7x = 14        divide both sides by -7

                                                                 x = -2 

 Feb 28, 2019
edited by ElectricPavlov  Feb 28, 2019
 #8
avatar+67 
-1

i think you accidentally multiplied by 7 instead of -7

DivideByZero  Feb 28, 2019
edited by DivideByZero  Feb 28, 2019
 #9
avatar+194 
0

Step 1: Simplify both sides of the equation.

−5(x−7)=49

 

(−5)(x)+(−5)(−7)=49(Distribute)

 

−5x+35=49

Step 2: Subtract 35 from both sides.

 

−5x+35−35=49−35

 

−5x=14

 Step 3: Divide both sides by -5.

 

\(\frac{-5x}{-5}=\frac{14}{-5}\)

 

x= -14/5

 

answer is x=-14/5     cool

 Feb 28, 2019
 #10
avatar
0

Big Brother, where does the problem say to multiply anything by –5 ? 

 Feb 28, 2019

35 Online Users

avatar
avatar